Enhancing Stratigraphic Geomodelling through Integration of Relative Geological Time and Spectral Decomposition: A Case Study from the Volve Field - Zahra, Dinanti Syafirani; Agustine, Eleonora; Hidayat, Ginanjar; Ramadani, Rafiki; Atthaillah, Luthfi Tanton (Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to enhance stratigraphic interpretation and geomodel construction through the integration of Relative Geological Time (RGT) and spectral decomposition in the Volve Field, North Sea. Conventional seismic interpretation often faces limitations in identifying subtle stratigraphic features such as channels and thin layers due to limited vertical resolution. To address this issue, RGT was applied to generate a stratigraphic framework with dense horizons based on relative geological time, followed by spectral decomposition using Short-Time Fourier Transform (STFT) and Continuous Wavelet Transform (CWT) to improve vertical resolution and delineate depositional features. The results show that the RGT-based stratigraphic framework successfully identified major horizons from Jurassic to Cenozoic intervals, highlighting depositional evolution within the study area. Spectral decomposition analysis at selected frequencies revealed sinuous channel geometries within the Sleipner and Hugin formations. Comparison between methods indicates that STFT provides more laterally continuous channel delineation, while CWT is more sensitive to local amplitude variations. RGB blending further enhanced visualization of channel features and improved geobody extraction. The integrated interpretation produced a three-dimensional geomodel of channel geobodies, indicating fluvio-deltaic to shallow marine depositional systems with significant lateral heterogeneity. This study demonstrates that integrating RGT and spectral decomposition improves stratigraphic interpretation, enhances geobody delineation, and reduces uncertainty in reservoir characterization. The proposed workflow can be applied to other complex depositional systems to improve stratigraphic geomodeling and reservoir analysis.